OPTIMIZING KEYWORD SEARCH FOR SEARCH ENGINES USING BLOCKCHAIN TECHNOLOGY - Bharti Aggarwal; Dinesh Rai; Naresh Kumar (Proceedings on Engineering Sciences)
The traditional SEO landscape, reliant on algorithmic changes and privacy concerns, demands new solutions. This research explores the integration of blockchain technology into SEO to boost website visibility without compromising user privacy. Utilizing blockchain-powered search engines, the author propose a novel approach that prioritizes transparency, trust, and secure data control. Through the intricate recording of user interactions on the blockchain, users benefit from relevant search results and enhanced privacy, addressing contemporary data protection concerns. The multifaceted evaluation, employing TF-IDF and cosine similarity across three datasets, demonstrates the efficacy of this approach in optimizing website visibility while safeguarding user data. Ultimately, this research paves the way for a future where SEO and blockchain technology collaborate harmoniously, transforming digital marketing and data protection in the evolving digital landscape.